Rapid signaling reactivation after targeted BRAF inhibition predicts the proliferation of individual melanoma cells from an isogenic population - Payam Khoshkenar (Nature Portfolio, 2021)
Abstract Cancer cells within tumors display a high degree of phenotypic variability. This variability is thought to allow some of the cells to survive and persist after seemingly effective drug treatments. Studies on vemurafenib, a signaling inhibitor that targets an oncogenic BRAF mutation common in melanoma, suggested that cell-to-cell variation in drug resistance, measured by long-term proliferation, originates from epigenetic differences in gene expression that pre-exist treatment. However, it is still unknown whether reactivation of signaling downstream to the inhibited BRAF, thought to be a key step for resistance, is heterogeneous across cells. While previous studies established that signaling reactivation takes place many hours to days after treatment, they monitored reactivation with bulk-population assays unsuitable for detecting cell-to-cell heterogeneity. We hypothesized that signaling reactivation is heterogeneous and is almost instantaneous for a small subpopulation of resistant cells. We tested this hypothesis by monitoring signaling dynamics at a single-cell resolution and observed that despite highly uniform initial inhibition, roughly 15% of cells reactivated signaling within an hour of treatment. Moreover, by tracking cell lineages over multiple days, we established that these cells indeed proliferated more than neighboring cells, thus establishing that rapid signaling reactivation predicts long-term vemurafenib resistance.